A model driven method for service composition modelling: a case study. (21st July 2006) - De Castro, Valeria; Marcos, Esperanza; Lopez Sanz, Marcos
In recent years, innovation in technologies such as XML, web services and component-based development has led to interest in business processes. For this reason several languages for designing and implementing business processes, such as Business Process Execution Language for Web Services (BPEL4WS), have been created. However, one weakness of these languages is that they are difficult for business analysts to use in the early stages of the web information systems development process. In this work, we present a model-driven method for service composition modelling. The method defines a process, new models and the mappings between them. The process first identifies the services that will be offered to the user and then allows obtaining a service composition model, which facilitates the mapping to a specific web services composition language. The proposed method is illustrated through a case study of a web information system for the management of medical images.